2004
DOI: 10.1007/s10327-004-0117-8
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effect of potassium silicate on powdery mildew of strawberry in hydroponics

Abstract: From 1996 to 1997 ) was tested at 0, 25, 50, and 100 mg l Ϫ1 in hydroponics to control powdery mildew. Other elements were added in the usual amounts, and the strawberries were cultivated hydroponically in a greenhouse for 4 months (from October to January). The powdery mildew spread in the control plot, but little mildew developed in the plot with 25 mg l Ϫ1 silicate, and none in plots with more than 50 mg l Ϫ1 silicate. The suppressive effect lasted for about 4 months on fruits and even longer on leaves. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 10 publications
0
39
0
1
Order By: Relevance
“…Besides, it also promotes the physiological activity and growth of plants and induces disease and stress resistance in plants (Garver et al 1998 ;Kanto et al 2004 ). Since the effect of silica varies with the physiological environment, it has not been registered as an agrochemical.…”
Section: Nano Silicamentioning
confidence: 99%
“…Besides, it also promotes the physiological activity and growth of plants and induces disease and stress resistance in plants (Garver et al 1998 ;Kanto et al 2004 ). Since the effect of silica varies with the physiological environment, it has not been registered as an agrochemical.…”
Section: Nano Silicamentioning
confidence: 99%
“…Silicon had beneficial effects on strawberry plants and may serve as an alternative to fungicides for controlling powdery mildew when supplied as a foliar spray of potassium and sodium silicate. Kanto et al (2004Kanto et al ( , 2007 and Wang and Galletta (1996) have recorded similar results about the strawberry-powdery mildew patho-system. However, root application of silicon could not reduce the disease severity in strawberry (Bowen et al, 1992).…”
Section: Powdery Mildewmentioning
confidence: 54%
“…Suppressive effect of silicon against plant pathogens has been known for many years (Cherif et al, 1994;Kanto et al, 2004) especially for diseases in rice plants (Datnoff et al, 1997). Present study revealed that soluble silicon has a suppressive effect on downy mildew in bitter gourd leaves.…”
Section: Discussionmentioning
confidence: 65%